Evaluation of peripheral vertigo: an observational vertigo - Sarkar, Mahadev; Barman, Dipjyoti; Shekhawat, Sunaina (International Journal of Research in Medical Sciences, 2024)
Background: Vertigo (internal) refers to the perception of self-motion even when there is no actual movement or the perception of distorted self-motion during normal motion of the head. Approximately 6.5% of individuals may encounter peripheral vestibular issues at some stage during their lifetimes. Methods: All patients attending the outpatient department of ENT and SMCH with the chief complaint of vertigo or dizziness had been subjected to a general physical examination, local examination of the ear, nose, and throat, examination of the vestibular system, postural tests, and cerebellar function tests. Pure Tone Audiometry, VNG (Videonystagmography), and radiological investigations as per requirement. Results: The study included 38 patients diagnosed with peripheral vertigo throughout the course of one year. Benign Paroxysmal Positional Vertigo (BPPV) was the most common condition (60.5%), followed by Meniere’s disease (7.9%) and acute vestibular neuritis (13.2%). Chronic Bilateral vestibulopathy, persistent perceptual postural dizziness (PPPD), and mobile third window phenomenon were less prevalent. Conclusions: This study concludes that early diagnosis and appropriate treatment can prevent peripheral vertigo, which is more common in the elderly population and compromises their quality of life.